A Comparative Clinical Study of Phalatrikadi Kwath and Nyagrodhadi Kwath in Madhumeha w.s.r.t. Diabetes Mellitus. - More, Hrutuja B; Dharmannvar, Girish; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: In modern era changing lifestyle like alasya, diwaswanpa, environmental changes, faulty eating habits like madhur – guru ahara etc are leading to Diabetes mellitus. Diabetes mellitus is metabolic disorder of multiple etiology characterized by Hyperglycemia, with disturbance of carbohydrate, fat, protein metabolism that can lead to serious complications such as cardiovascular disease, diabetic retinopathy and Nephropathy etc. Because of complication of allopathic treatment peoples are preferring ayurvedic treatment. For treatment here attempt is being made with kwath preparation as usually ghruta preparation is widely used. Aim and objectives: 1) To study effect of phalatrikadi kwath and Nyagrodhadi kwath in madhumeha. 2) To compare effect of phaltrikadi kwath and Nyagrodhadi kwath in madhumeha. Material and method: In this study 40 patients were selected and divided into 2 group with 20 patients each. Group A was administered with phalatrikadi kwath and group B with Nyagrodhadi kwath 40ml respectively for 28 days. After treatment results were assessed on basis of subjective and objective criteria by using unpaired T test. Observation and result: Comparative analysis of the overall effect of the treatments in both the groups was done by statistically with unpaired t test. The test shows that the treatment is significant in Group B when compared to Group A. Group A overall result is 85.88% and Group B overall result is 92.49% Conclusion: The overall study reveals that group B Nyagrodhadi kwath showed more efficacy.